PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN MENGGUNAKAN JASA GRAB DI KOTA BANJARBARU - Akhmad Samhudi; Siti Raesa Rizki Pardani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to examine: (1) To determine and analyze the effect of Service Quality on Decisions to Use Grab services in Banjarbaru. (2) To find out and analyze the effect of price on the decision to use Grab services in Banjabaru. (3) To find out and analyze the effect of Services Quality and Price on Decisions to Use Grab services in Banjarbaru. The indicators for each variable are the first service quality indicators are tangible (tangible), reliability (reliability), responsiveness (responsiveness), assurance (guarantee), empathy (empathy). From the price variable the indicators are price affordability, price suitability with product quality, price competitiveness, price suitability with benefits. And from the use decision variables are product selection, brand selection, dealer selection, time of purchase, number of purchases, payment methods. This study uses quantitative analysis. The data analysis method used ia multiple linear regression analysis technique, classical assumption test, F test, t test, coefficient of determination. The results of this study indicate that service quality and price simultaneously affect the decision to use Grab services in Banjarbaru. Price has a partial effect on the decision to use Grab services in Banjarbaru.